Guía metodológica para la selección de proveedores DBaaS en Pymes - Vargas-Corredor, Fabián Leonardo; Quevedo-Reyes, Jorge Enrique; González-Sanabria, Juan Sebastián; Suárez-Barón, Marco Javier (Revista Científica, 2020)
The importance that has acquired the trend of database-as-a-service (DBaaS) and the relationship that providers have directly in the management of information when offering a service in the cloud, are key factors in the management of information. The negative impact on monetary resources, performance and information security has inspired an analysis on cloud service acquisition in order to mitigate errors in DBaaS adoption. The present work intends to propose the development of a methodological guide that strengthens the DBaaS acquisition processes in SMEs, managing to minimize its impact on the loss or disuse of monetary resources, infrastructure, and security. For this purpose, a document review is carried out, including documents from 2008 to 2018, a period in which countries with high performance levels in research on cloud computing and database management services published significantly. The creation of a methodological guide in the selection of DBaaS providers in SMEs, establishes methods, paths and outstanding strategies when acquiring a DBaaS service. The priority is to know in detail how the service level agreements oriented to the adoption of Cloud Services are developed and managed.